Asthma in United States Olympic athletes who participated in the 1996 Summer Games - Weiler, J. M.; Layton, T.; Hunt, M. (Journal of Allergy and Clinical Immunology, 1998)
BACKGROUND: Asthma prevalence appears to be increasing in the general population. We sought to determine whether asthma prevalence has also increased in highly competitive athletes. OBJECTIVE: Our aim was to determine how many United States Olympic athletes who were chosen to participate in the 1996 Summer Olympic Games had a past history of asthma or symptoms that suggested asthma or took asthma medications. METHODS: We analyzed responses to questions that asked about allergic and respiratory diseases on the United States Olympic Committee (USOC) Medical History Questionnaire that was completed by all athletes who were chosen to represent the US at the 1996 Summer Olympic Games in Atlanta. RESULTS: Of the 699 athletes who completed the questionnaire, 107 (15.3%) had a previous diagnosis of asthma, and 97 (13.9%) recorded use of an asthma medication at some time in the past. One hundred seventeen (16.7%) reported use of an asthma medication, a diagnosis of asthma, or both (which was our basis for the diagnosis of asthma). Seventy-three (10. 4%) of the athletes were currently taking an asthma medication at the time that they were processed in Atlanta or noted that they took asthma medications on a permanent or semipermanent basis and were considered to have active asthma. Athletes who participated in cycling and mountain biking had the highest prevalence of having been told that they had asthma or had taken an asthma medication in the past (50%). Frequency of active asthma varied from 45% of cyclists and emountain bikers to none of the divers and weight lifters. Only about 11% of the athletes who participated in the 1984 Summer Olympic Games were reported to have had exercise-induced asthma on the basis of other criteria that may have been less restrictive. On the basis of these less restrictive criteria, more than 20% of the athletes who participated in the 1996 Olympic Games might have been considered to have had asthma. CONCLUSIONS: Asthma appeared to have been more prevalent in athletes who participated in the 1996 Summer Games than in the general population or in those who participated in the 1984 Summer Games. This study also suggests that asthma may influence the sport that an athlete chooses.